An important factor for the water gas shift reaction activity of Cu-loaded cubic Ce0.8Zr0.2O2 catalysts - 장원준; Hyun-Seog Roh; 정대운 (Environmental Engineering Research, 2018)
The Cu loading of a cubic Ce0.8Zr0.2O2-supported Cu catalyst was optimized for a single-stage water gas shift (WGS) reaction. The catalyst was prepared by a co-precipitation method, and the WGS reaction was performed at a gas hourly space velocity of 150,494 h−1. The results revealed that an 80 wt% Cu-Ce0.8Zr0.2O2 catalyst exhibits excellent catalytic performance and 100% CO2 selectivity (XCO = 27% at 240°C for 100 h). The high activity of 80 wt% Cu-Ce0.8Zr0.2O2 catalyst is attributed to the presence of abundant surface Cu atoms and the low activation energy of the resultant process.
Keywords: Activation energy; Ce0.8Zr0.2O2; Cu atoms; Cu loading